Association Between Medicaid Status, Social Determinants of Health, and Bariatric Surgery Outcomes. Issue 1 (7th March 2021) - Liu, Natalie; Venkatesh, Manasa; Hanlon, Bret M.; Muraveva, Anna; Johnson, Morgan K.; Hanrahan, Lawrence P.; Funk, Luke M.
Abstract : Objective: To compare outcomes after bariatric surgery between Medicaid and non-Medicaid patients and assess whether differences in social determinants of health were associated with postoperative weight loss. Background: The literature remains mixed on weight loss outcomes and healthcare utilization for Medicaid patients after bariatric surgery. It is unclear if social determinants of health geocoded at the neighborhood level are associated with outcomes. Methods: Patients who underwent laparoscopic sleeve gastrectomy (SG) or Roux-en-Y gastric bypass (RYGB) from 2008 to 2017 and had ≥1 year of follow-up within a large health system were included. Baseline characteristics, 90-day and 1-year outcomes, and weight loss were compared between Medicaid and non-Medicaid patients. Area deprivation index (ADI), urbanicity, and walkability were analyzed at the neighborhood level. Median regression with percent total body weight (TBW) loss as the outcome was used to assess predictors of weight loss after surgery. Results: Six hundred forty-seven patients met study criteria (191 Medicaid and 456 non-Medicaid). Medicaid patients had a higher 90-day readmission rate compared to non-Medicaid patients (19.9% vs 12.3%, P < 0.016). Weight loss was similar between Medicaid and non-Medicaid patients (23.1% vs 21.9% TBW loss, respectively; P = 0.266) at a median follow-up of 3.1 years. In adjusted analyses, Medicaid status, ADI, urbanicity, and walkability were not associated with weight loss outcomes. Conclusions: Medicaid status and social determinants of health at the neighborhood level were not associated with weight loss outcomes after bariatric surgery. These findings suggest that if Medicaid patients are appropriately selected for bariatric surgery, they can achieve equivalent outcomes as non-Medicaid patients. Abstract : Mini-abstract: The relationship among Medicaid status, social determinants of health, and bariatric surgery outcomes is unclear. Using electronic health record data and social determinant variables geocoded at the neighborhood level, we found that Medicaid status, socioeconomic deprivation, household location (rural vs urban), and neighborhood walkability were not associated with weight loss outcomes after bariatric surgery. However, Medicaid patients had higher readmission rates within 90 days of surgery. Supplemental Digital Content is available in the text.